THE IMPACT OF ELECTRONIC HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL EXCELLENCE IN JORDANIAN ELECTRICITY COMPANY: THE MEDIATING ROLE OF ORGANIZATIONAL LOYALTY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The study aimed to teach the electronic practices of human resources management in the Jordanian Electric Power Company regulatory organization and the mediating role of organizational loyalty by following the descriptive analytical approach. The primary data was collected during a questionnaire that was developed and distributed to the study sample consisting of managers, their assistants, heads of departments, and the administrative subject in the company's main center, which numbered (196) employees. For data analysis and hypothesis testing, the study used appropriate statistical methods using the Statistical Package for Social Sciences (SPSS) and (AMOS) programs. The study reached a set of results, the most important of which was the presence of a statistically significant effect of the electronic practices of human resource management (e-recruitment, training, and e-development, Electronic performance evaluation, electronic compensation) on organizational excellence with the presence of organizational loyalty as a mediating variable in the National Electric Power Company. The study recommended increasing the level of interest in applying electronic practices for human resources management, especially concerning performance evaluation, training, and development processes, whereby electronic programs, means, and technologies can be used to conduct an objective and professional evaluation of human resources following professional and administrative standards and to publish educational and training materials and make them available to employees through its website. Increasing the company's level of interest in achieving organizational excellence, By adopting procedures that contribute to building a distinguished leadership, encourage the establishment of a distinct organizational culture, and provide adequate support and motivation to subordinates.